Pharmacologic treatments in preclinical tinnitus models with special focus on Ginkgo biloba leaf extract EGb 761® - Barth, Stephan W.; Lehner, Martin D.; Dietz, Gunnar P.H.; Schulze, Holger (Molecular and Cellular Neuroscience, 2021)
Tinnitus is defined as the perception of sound in the absence of external acoustic stimuli. Frequent comorbidities or associated factors are depression, anxiety, concentration problems, insomnia, resignation, helplessness, headache, bruxism, or social isolation, just to name a few. Although many therapeutic approaches have already been tested with varying success, there still is no cure available for tinnitus. The search for an effective treatment has been hampered by the fact that the mechanisms of tinnitus development are still not fully understood, although several models are available and discussed in this review. Our review will give a brief overview about preclinical models, presenting the heterogeneity of tinnitus sub-types depending on the different inner ear and brain structures involved in tinnitus etiology and pathogenesis. Based on these models we introduce the different target structures and transmitter systems implicated in tinnitus development and provide an extensive overview on preclinical drug-based therapeutic approaches that have been explored in various animal models. As the special extract from Ginkgo biloba leaves EGb 761® has been the most widely tested drug in both non-clinical tinnitus models as well as in clinical trials, a special focus will be given to EGb 761®. The efficacy of terpene lactones, flavone glycosides and proanthocyanidines with their distinct contribution to the overall efficacy profile of the multi-constituent drug EGb 761® will be discussed.
CRIS-Team Scopus Importer:2021-10-08
Keywords: Gerbil; Hearing research; Inner ear; Medication; Mouse; Pharmacology; Plant extract; ginkgo; translational; Rat; Rodent model